Environmental Visual Pollution and Its Impact on General Appearance and Aesthetic Image of City Observational Study.: City of Sebha. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
Environmental pollution in all it,s forms is the reason of the destruction of the vital component on the surface of the Eart, This is in addition to its harmful effects on public health and visual pollution ys one of the most important forms of pollution that third world countries suffer from it, Especialy with the increase in technical, industrial, and civilized progress, this is in addition to the growing population, As well as lack of environmental awareness and poor behavior in preserving the environment, and the absence of legal deterrment to limii environmental damage. The city of Sebha (southwest Libya) is among the cities that suffer from visual environmental pollution, As this city was affected by the deteriorating in the political, economic, social and service condition. Which lead to the loss of aesthetic, artistic and visual aspects of this city. This study attempts to monitor the manifestations if visual pollution and determaine their causes through viewing ""observational study"" this was done using a digital camera. (DCc540) , to determine the extent of this phenomenon and the extent of its danger to the environment and human life. This study also aimed to develop suggestions to improve that aesthetic and visual image in line with the nature of the city, and the general culture of its residents. Through this study, it was concluded that the phenomenon of visual pollution is extremely danagerous at all levels, whether visual pollution is physical, such as poor urban design and the inconsistency of modern building with old ones and large reduction in green areas or behavioral visual pollution: such as randomly spreading rubbish bins and heaps of rubbish outside, them in addition to the presence of old dilapidated cars between the roads and residential neighborhood, also among those manifestations is the presence of trucks loaded with goods that are not appearance. Not to mention the randomly installed air conditioners on the walls of buildings and paint the buildings in different colors, other than that, there are many improper behavioral manifestations resulting from lack of awareness.This study concluded with a number of recommendations related to the problem under study and suggested appropriate solution to solve it.
Keywords: Visual Pollution; Sebha City; Physical Visual Pollution; Behavioral Visual Pollution